Representations of Colombian Andean farmers on climate change and mitigation and adaptation strategies - Rodríguez,José de Jesús Núñez (2021)
Abstract: This article presents the findings of research conducted in a rural community located in Norte de Santander Department, Colombia, on farmers' representations of the impacts of climate change. The analysis of the behavior of temperature and average rainfall in the period 1985-2015 was put together concerning the local knowledge of the farmers. The approach was developed through 56 multiple choice questions surveys done to 144 producers intentionally selected from a group of 1,933 farmers, analyzed with descriptive and inferential statistical techniques. The findings indicate a broad opinion by farmers of the effects of climate change due to the gradual increase in temperature that causes changes in the bimodal system and intensity of rainfall; reduction in agricultural and livestock production, product quality and quantity; intensification of pest and disease attacks; reduction in water sources and water quality; extinction and migration of species of flora and fauna; and effects on the family’s comfort during work and rest hours, health and hygiene. Likewise, local strategies and the participation of public institutions in the mitigation and adaptation to climate change are evident.